Patient understanding of drug risks: an evaluation of medication guide assessments. (23rd March 2015) - Knox, Caitlin; Hampp, Christian; Willy, Mary; Winterstein, Almut G.; Pan, Gerald Dal
Abstract: Purpose: When a Medication Guide (MG) is part of Risk Evaluation and Mitigation Strategy (REMS), manufacturers assess the effectiveness of MGs through patient surveys, which have not undergone systematic evaluation. We aimed to characterize knowledge rates from these patient surveys, describe their design and respondent characteristics, and explore predictors of acceptable knowledge rates. Methods: We analyzed MG assessments submitted to the Food and Drug Administration from September 2008 through June 2012. We evaluated the prevalence of specific characteristics, and calculated knowledge rates, whereby we defined "acceptable knowledge" when ≥ 80% of respondents correctly answered questions about the primary drug risk. Univariate logistic models were used to investigate the predictors of acceptable knowledge rates. Results: We analyzed the first completed MG assessment for each drug with a patient survey, resulting in 66 unique MG assessments. The mean knowledge rate was 63.8%, with 20 MG assessments (30.3%) achieving the 80% threshold. Compared to assessments that did not reach acceptable knowledge rates, those that did were more likely associated with additional REMS elements (e.g. Elements to Assure Safe Use or Communication Plans). Other factors, including mean age, reading or understanding the MG, and being offered or accepting counseling were not associated with knowledge rates. There was considerable variation in the design of MG assessments. Conclusions: Most MG assessments did not reach the 80% knowledge threshold, but those associated with additional interventions were more likely to achieve it. Our study highlights the need to improve patient‐directed information and the methods of assessing it. Copyright © 2015 John Wiley & Sons, Ltd.